2009
DOI: 10.1016/j.ab.2008.10.049
|View full text |Cite
|
Sign up to set email alerts
|

A radiation target method for size determination of supercoiled plasmid DNA

Abstract: Supercoiled DNA plasmids were exposed in the frozen state to high energy electrons. Surviving supercoiled molecules were separated from their degradation products (e.g., open circle and linear forms) by agarose gel electrophoresis and subsequently quantified by staining and image analysis. Complex survival curves were analyzed using radiation target theory, yielding the radiation-sensitive mass of each form. One of the irradiated plasmids was transfected into cells, permitting radiation analysis of gene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…27 Alternatively, the DNA backbone may have limited the transmission of damage in cis, as suggested for the backbone of frozen RNA. 41,53 The b2 deletion mutant of bacteriophage λ has a genome size approximately 15% less than the wild type, but the phage particle is the same size as the wild type. Earlier, it was reported that λ b2 was more resistant to UV irradiation than wild type λ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Alternatively, the DNA backbone may have limited the transmission of damage in cis, as suggested for the backbone of frozen RNA. 41,53 The b2 deletion mutant of bacteriophage λ has a genome size approximately 15% less than the wild type, but the phage particle is the same size as the wild type. Earlier, it was reported that λ b2 was more resistant to UV irradiation than wild type λ.…”
Section: Discussionmentioning
confidence: 99%
“…A radiation target method, using semi-quantitative measures of DNA damage on agarose gels, for estimating the size of supercoiled plasmid DNA was reported recently. 41 In that work, the size of the supercoiled plasmid was predicted accurately with a one-hit model, presumably because a single hit relaxed the supercoiled molecule. The nature of the assay does not allow the determination of whether the damage was from a single hit or was not propagated in the DNA molecule.…”
Section: Introductionmentioning
confidence: 98%
“…Intergel variability can be reduced by loading a complete standard curve on each gel. 33 Although this approach does produce more accurate results, the capacity to analyze large sample sets is hampered by the need to accommodate standards on each gel, thereby reducing the number of lanes available for samples. Even with the use of standard curves on each gel and optimization of staining conditions, significant variability is typically observed in background staining within a single gel, particularly at the edges of the gel.…”
Section: Discussionmentioning
confidence: 99%
“…Agarose gels were used to analyze sample degradation after processing as described in our previous work 32. First, the concentration of each DNA sample was quantified by absorbance at 260 nm to ensure that 300 ng was loaded into each lane of a 0.5% agarose gel.…”
Section: Methodsmentioning
confidence: 99%